Вплив глобалізації на розвиток управлінського обліку - Безверхня, Юлія Вікторівна; Безверхняя, Юлия Викторовна; Bezverkhnya, Yuliia (My University, 2015)
Uk: У статті визначені основні перспективи розвитку управлінського обліку, проаналізовано вплив глобалізації на прийняття управлінських рішень, обґрунтовано впровадження стратегічного управлінського обліку, зазначено, що в умовах світової глобалізації розвиток стратегічного управлінського обліку є найбільш перспективним напрямком удосконалення облікових процесів на підприємствах. En: n the article the basic prospects of development of administrative account are certain, influence of globalization on the acceptance of administrative decisions is analysed, introduction of strategic administrative account is reasonable, in the conditions of world globalization development of strategic administrative account is the most perspective direction of improvement of registration processes on enterprises is indicated. A research aim is a study of influence of world globalization on administrative registration processes on enterprises, and also prospects of development of administrative account in similar terms. The allocation of the strategic account due to the rapid strengthening of the role of long-term planning, strategic management. The main difference between strategic management accounting from a traditional is that in addition to the identification and analysis of internal factors, strategic accounting requires accounting, analysis and discussion of external factors, including both financial and non-financial indicators. In the period of globalization for safety and increase of competitive edges of company it is necessary to create the system of administrative account, oriented to longterm development of enterprise, and sent to engaging in the enterprise of perspective and profitable market niches. Such system is a strategic administrative account that will allow to the enterprise maximally effectively to use present resource, financial, technological and innovative potential for the achievement of financial firmness today and in the future. Strategic management accounting as a science is relatively young and should be investigated both from the point of view of clarifying its theoretical component, and from the point of view of development of methods of strategic management accounting. Ru: В статье определены основные перспективы развития управленческого учета, проанализировано влияние глобализации на принятие управленческих решений, обосновано внедрение стратегического управленческого учета, указано, что в условиях мировой глобализации развитие стратегического управленческого учета является наиболее перспективным направлением усовершенствования учетных процессов на предприятиях.
The impact of globalization on the development of management accounting
Влияние глобализации на развитие управленческого учета
Keywords: глобалізація; управлінські рішення; стратегічний управлінський облік; глобалізація; globalization; administrative decisions; trategic administrative account; глобализация; управленческие решения; стратегический управленческий учет